Chemical modification of yellow and purple corn starch: Effect on its resistance to in vitro digestion - Rojas Vera, Byron Andrés (2025)
Corn stands out for its large crop volume, high yield and starch content, an important source of energy. Given the need to preserve the health of the consumer and provide various uses for this polysaccharide, the objective of this work was to apply two modification methods (acid: citric acid and OSA: octenyl succinic anhydride) on corn starch of two varieties (yellow and purple), to increase the content of resistant starch (RS) to digestion, and thus, select a treatment that allows improving its prebiotic potential. The extracted starches had a purity between 86,25% and 93,78%, indicating good extraction efficiency. Yellow corn allowed the highest yield in obtaining native and modified starch by acid method and OSA method (47,97% to 56,07%); compared to the yield achieved from purple corn (39,06% to 45,98%). The highest RS content (95,30%) was observed in purple corn starch modified with OSA, and the highest amylose content (AC) was observed in the starch of yellow and purple corn treated with citric acid. in a hot humid environment (37,09 to 41,89%) (p < 0,05); which indicates that, mainly purple corn modified by OSA can act as an additive with great prebiotic potential, useful for designing new functional foods.